THE SPECIFICITY OF INTERFERON INDUCTION IN CHICK EMBRYO CELLS BY HELICAL RNA - Colby, Clarence (1969)
Treatment of chick embryo cells growing in culture with rI:rC and many other RNA-like polymers results in the induction of interferon. DEAE dextran is required to facilitate the uptake of the RNA into the cells. Interferon-inducing activity is found with a variety of double-stranded helical polynucleotides, provided that all the sugar residues are ribose. However, the effectiveness of different active polynucleotides at a given concentration varies considerably. The differences in activity among the various polynucleotides do not appear to reflect differences in the rate or amount of uptake into the cells or in the rate of intracellular breakdown. Thehigh degree of specificity of the induction process is consistent with the existence of a specific intracellular receptor site, which may be a protein.